2017
DOI: 10.1016/j.nano.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Effective encapsulation and biological activity of phosphorylated chemotherapeutics in calcium phosphosilicate nanoparticles for the treatment of pancreatic cancer

Abstract: Drug resistant cancers like pancreatic ductal adenocarcinoma (PDAC) are difficult to treat, and nanoparticle drug delivery systems can overcome some of the limitations of conventional systemic chemotherapy. In this study, we demonstrate that FdUMP and dFdCMP, the bioactive, phosphorylated metabolites of the chemotherapy drugs 5-FU and gemcitabine, can be encapsulated into calcium phosphosilicate nanoparticles (CPSNPs). The non-phosphorylated drug analogs were not well encapsulated by CPSNPs, suggesting the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Chen et al reported that down-regulation of FAM83B in PDAC cells contributed to G0/G1 phase arrest and inhibition of cell proliferation 56 ; Liu et al discovered YY1 suppressed proliferation and migration of PDAC by regulating the CDKN3 / MdM2 / P53 / P21 signaling pathway 57 . Numerous biomarkers were reported to impact PDAC via cell cycle pathway, including the 10 hub real genes mentioned above 58 - 60 . Therefore, further exploration of cell cycle and associated genes was of enormous significance.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that down-regulation of FAM83B in PDAC cells contributed to G0/G1 phase arrest and inhibition of cell proliferation 56 ; Liu et al discovered YY1 suppressed proliferation and migration of PDAC by regulating the CDKN3 / MdM2 / P53 / P21 signaling pathway 57 . Numerous biomarkers were reported to impact PDAC via cell cycle pathway, including the 10 hub real genes mentioned above 58 - 60 . Therefore, further exploration of cell cycle and associated genes was of enormous significance.…”
Section: Discussionmentioning
confidence: 99%
“…The TEM observations of the finer ultrastructure during synthesis of the CPSNPs lead us to hypothesize that encapsulation of the various active agents was mediated by adsorption on the precursor nanoparticle clusters that subsequently agglomerate into the final particle. This ultimately lead to the striking revelation that phosphorylated forms of the drugs would encourage robust encapsulation through phosphate on the drug molecule binding to excess calcium sites on the precursor nanoparticles ( Figure 2) [1,2]. This hypothesis was verified by an increase in encapsulation efficiency from < 1 mole% for prior formulations to 60 to 95 mole% for the phosphorylated drugs.…”
mentioning
confidence: 90%
“…. Synthetic scheme for CPSNPs using reverse micelles with Os-stained CPSNPs revealing the 1-3 nm diameter ultra microstructure of the 50nm diameter CPSNPs through which the phosphorylated compounds obtain high encapsulation efficiency [1]. The aptamer 1153 targeting was more effective than gastrin 16 targeting with both active targeting more effective than passive mPEG-CPSNPs.…”
mentioning
confidence: 98%
See 2 more Smart Citations